Studi Perbandingan Regulasi Pembajakan Daring (Online) di Indonesia dan Amerika Serikat - Adelaide Kathya Setianto; Kholis Roisah (Journal of Creative Student Research, 2026)
This study examines the differences in the regulatory frameworks for online piracy between Indonesia and the United States, which have implications for the level of legal certainty, platform liability, and the effectiveness of law enforcement in the digital space. The main issue lies in the lack of integration in Indonesia’s regulatory framework compared to the more comprehensive system in the United States. This study employs a normative legal approach using comparative law methods, analyzing legislation, legal doctrines, and law enforcement practices in both countries through a literature review. The research findings indicate that Indonesia still faces regulatory fragmentation, limitations in platform liability regulations, and weak enforcement implementation, despite provisions in the Copyright Law and the ITE Law along with their implementing regulations. In contrast, the United States, through the Digital Millennium Copyright Act (DMCA), has developed a more structured mechanism, particularly through the safe harbor principle and the notice-and-takedown system, which enhance legal certainty and the effectiveness of legal protection. The effectiveness of regulation is influenced by the integration of norms, institutional capacity, and adaptation to developments in digital technology. Therefore, regulatory reform in Indonesia is needed that is more adaptive, integrated, and responsive to the dynamics of online piracy.